IOT based water consumption meter for domestic / Muhammad Afif Shazmin Azmi - Azmi, Muhammad Afif Shazmin (2019)
This study was conducted to analyse the water consumption for domestic purposes using the hall's effect sensor and the Internet of Things (loT) for the regular water meter. Currently, most of water consumer was not aware of good water management. In other word, a method to save their water usage and any medium for analysing their consumption. Thus, in this work, new electronics graphical through smartphone to assist water consumer is introduced. The data on water consumption will assist the consumer to be more flexible in their saving as well as water usage. This method will display the amount of water and billings by employing YF-S201 and ESP8266 sensor. The result is analysed through "Thingspeak" application for data measurement. This finding show the data measured by YF-S201 sensor are approximately similar as the expected amount of water consumption.